The Effect of the Cooperative Integrated Reading and Composition (CIRC) Learning Model, with a Scientific Approach, on the Creative Thinking Skills of Students at SMK Negeri 3 Bandung - Firman Sanjaya; Sunata (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to determine the effect of the Cooperative Integrated Reading and Composition (CIRC) learning model, which is oriented toward a scientific approach, on the creative thinking skills of students at SMK Negeri 3 Bandung. The problem addressed in this study stems from students’ low levels of creative thinking, which are caused by a learning process that remains largely teacher-centered, resulting in students having few opportunities to develop ideas, engage in discussion, and discover alternative solutions to problems. This study employed a quantitative approach using a quasi-experimental method and a nonequivalent control group design. The research subjects consisted of an experimental class that used the CIRC learning model with a scientific approach and a control class that used a conventional learning model. Data were collected through creative thinking ability tests in the form of pretests and posttests. Data analysis was conducted using normality tests, homogeneity tests, t-tests, and N-Gain tests. The results of the study indicate that there was an improvement in students’ creative thinking skills after implementing the CIRC learning model. This is evidenced by the experimental class’s N-Gain score of 75.11%, which falls into the “high” category, while the control class achieved an N-Gain score of 16.54%, which falls into the “low” category. The results of the hypothesis test showed a significance value of 0.00 < 0.05, Thus, the use of the science-oriented CIRC learning model has a significant effect on students’ creative thinking skills. Therefore, the science-oriented CIRC learning model can serve as an alternative teaching method to enhance students’ creative thinking skills.